Using tourism as a mechanism to reduce poaching and hunting: a case study of the Tidong community, Sabah - Mohamed, Maryati; Hamzah, Zulhazman; Prideaux, Bruce; Saikim, Fiffy Hanisdah (Emerald Group Publishing Limited, 2016)
"In Sabah, Malaysia, illegal hunting has increased in recent years putting considerable pressure on large mammal populations. The causes for this phenomenon lie in increasing rural poverty, ineffective policies to regulate hunting, as well as a ready market for many wildlife products in the Chinese medicine markets. This paper examines how Community-Based Ecotourism has some potential to be used as a tool to reducing poaching using the Tidong community in Sabah as a case study. The key finding is that successful conservation outcomes for Community-Based Ecotourism projects are only sustainable over the long run if projects are structured to ensure that the local community is able to continue effective management once sponsoring organizations hand over control and that revenue from tourism does not decline. If tourist revenue declines communities may be forced to revert to previous practices reversing any initial conservation gains."